2012
DOI: 10.1016/j.jcot.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy in children: An overview

Abstract: Children Management a b s t r a c tA review article giving a brief synopsis of etiology, classification, diagnosis and management of cerebral in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 11 publications
0
30
0
4
Order By: Relevance
“…Currently, CP is recognized as being the most common cause of serious permanent physical disability in childhood, although the prospect of survival in children with severe disability has increased in recent years. Cerebral palsy is associated with sensory deficits, cognitive deficits, communication and motor disabilities, behavioral problems, seizure disorders, pain and secondary musculoskeletal problems, with spastic paresis being one of the most common forms of presentation [5,6], affecting the magnitude of movement and motor control [7,8], including the craniocervical region. Thus, head movement alterations can impair temporomandibular joint functions [9], and increase the risk of falls [10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CP is recognized as being the most common cause of serious permanent physical disability in childhood, although the prospect of survival in children with severe disability has increased in recent years. Cerebral palsy is associated with sensory deficits, cognitive deficits, communication and motor disabilities, behavioral problems, seizure disorders, pain and secondary musculoskeletal problems, with spastic paresis being one of the most common forms of presentation [5,6], affecting the magnitude of movement and motor control [7,8], including the craniocervical region. Thus, head movement alterations can impair temporomandibular joint functions [9], and increase the risk of falls [10].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of CP is not fully understood, but might be related to events that occur during neural development triggered by pre‐, peri‐ or postnatal factors . The main prenatal factor in the aetiology of CP is infections .…”
Section: Introductionmentioning
confidence: 99%
“…Socio-demographic details revealed that 70.8% of the total sample included were males and 29.2% were females. Researches show that the occurrence of cerebral palsy is greater in males compared to females with a ratio of 1.33:1 [11] .…”
Section: Discussionmentioning
confidence: 99%